School age sport and social agents: a preliminary study of the relationship between family, monitors and sportsmen and women in the province of León - Ruiz-Juan, F.; Zarauz Sancho, A. (FEADEF, 2012)
To study the differences between Spanish marathoners with the maximun and the lower mean score on the Running Addiction Scale (RAS-8), was categorized into quartiles the average scores on this scale for them (n = 1226) in several marathons of the Spanish geography. Then compared the differences in demographic, training and performance variables between the groups were. Were obtained valuable descriptive data of the sample and gender differences, and we concluded that the difference between the marathoner with higher values of negative addiction to running (not desirable) and the lowest negative addiction were, being a male, making both a significantly greater number of miles and days of training per week and hours per training, caring more for looking for a coach and have a best record nearly 3 hours and a half in the 6-7 marathons that have completed, compared with less concern about having a coach and to be his first marathon in runners with scoring minimum ANC. Was not expected that women would not had significant differences.